Chicago's Redevelopment Machine and Blues Clubs - Wilson, David (Springer International Publishing, 2018)
This book examines the conflict surrounding the latest redevelopment frontier in Chicago: the city's South Side blues clubs and blocks. Like Chicago, cities such as Cleveland, St. Louis, Boston, Washington D.C., Indianapolis, Milwaukee, and Philadelphia are experiencing a new redevelopment machine: one of tyrannizing and fear. Its actors are adroit at working via the creation of fear to "terror-redevelop" in these historically neglected neighborhoods. The book also discusses the powerful race and class-based politics in Chicago's blues clubs that resist such change. A "leisure as resistance" framework represents the latest innovative form of opposition to the transformation of these historic sites.